MOLLUSCA' BIODIVERSITY (GASTROPODA AND BIVALVIA) AS A BIO INDICATOR OF QUALITY OF WATER IN THE COASTAL ISLAND OF TUNDA ISLAND, BANTEN - Indria Wahyuni; Indah Juwita Sari; Bambang Ekanara (Biodidaktika : Jurnal Biologi dan Pembelajarannya, 2017)
The research has been done on Juli 2017 in the coastal region of Tunda Island. This study aims to determine the Biodiversity of Mollusca (Gastropoda and Bivalvia) As Bioindicator of Water Quality In Coastal Area of Tunda Island, Banten. Sampling consists of 2 observation stations, namely the mangrove coastal area (3 transects) and the seagrass coastal area (2 transects) determined by purposive sampling. The observation of each station is done by using the quadratic transect method with 100 m transect line distance, and in each transect line there are 5 observation plots measuring 1m2 x 1m2. The data analysis includes density, biodiversity, bio-indicators of water quality based on diversity index. Result of research on 5 transect found 45 type Mollusca which represent 2 class, that is Gastropoda class of 29 species Gastropoda joined in 14 Family. As for Bivalvia class found 16 species incorporated in 9 families. The total density of Mollusca is 541.2 ind / m2 which consists of 392.4 ind / m2 for Gastropoda class and 148.8 ind / m2 for Bivalvia class. Mollusca diversity was calculated using the diversity index of Shannon-Wienner (H '). The results of diversity index ranged from 3.1356 - 3.3314 with high category. Bioindicator of aquatic quality using diversity index indicates that the coastal area of Tunda Island belongs to a very mildly polluted category.